The Cooperative Principle in Fate: The Winx Saga Episode 1 - Fatizatulo Zega; Ambalegin (e-Journal of Linguistics, 2023)
The aim of this research is to analyze the cooperative principle inFate: The Winx Saga Episode 1 as data source. Researchers usedtheory of Grice to analyze the data. This research used descriptivequalitative method because the result would be described in words,sentences and paragraphs. Observational method was used in thisresearch along with non-participatory and note taking techniques.This research was found 57 data of four of cooperative principle.Maxim of quality with 11 data, maxim of quantity with 11 data,maxim of relation 18 data and maxim of manner with 17 data. Maximof relation was the most uttered and maxim quality and quantity werethe least uttered in the movie.